The effect of rose damascene extract on anxiety and sexual function of breastfeeding women: a randomized controlled trial - Akbarzadeh, Gohar; Abedi, Parvin; Jahanfar, Shayesteh; Mansurkhani, Hossein Sadeghi; Fakhri, Ahmad; Maraghi, Elham (Frontiers in Medicine, 2024)
Background Sexual dysfunction is prevalent among breastfeeding women. Objective This study was designed to evaluate the effect of Rose damascene extract on sexual function and anxiety of breastfeeding women. Materials and methods This was a randomized controlled trial. This study was conducted on 87 breastfeeding women who received either Rose damascene (n = 44) or placebo (n = 43) for eight weeks. The primary outcomes were sexual function and anxiety. A demographic questionnaire, and obstetric questionnaire, the Female Sexual Function Scale (FSFI), and the Spielberger questionnaire were used to collect the data. Chi-square test, independent t-test, and ANCOVA were used to analyze the data. Results In the intervention group, there was a significant increase in the scores of sexual desire, arousal, lubrication, orgasm, and sexual satisfaction, while the score of pain reduced significantly after eight weeks of intervention (p < 0.001). The mean total score of sexual function prior to the intervention was 19.61 ± 5.02 and 21.46 ± 3.08 in the intervention and control groups, respectively. After intervention, this score was improved in the intervention group compared to the control group (25.21 ± 1.62 vs. 21.82 ± 3, p < 0.001). The pre-intervention score of trait anxiety was 47.97 ± 4.68 and 48.44 ± 5.89 in the intervention and control groups, respectively, which was improved in the intervention group compared to the control group after intervention (51.63 ± 3.53 vs. 48.13 ± 5.57, p < 0.001). Although there was an improvement in the score of state anxiety in the intervention group compared to the control group, the difference was not statistically significant (43.31 ± 6.41 vs. 44.30 ± 8.87, p = 0.397). Conclusion Rose damascene could significantly improve the sexual functions of breastfeeding women. It also decreased the trait anxiety but failed to improve the state anxiety significantly. Using this herb is recommended to enhance sexual performance in breastfeeding women. Clinical trial registration https://www.irct.ir/trial/61375, identifier IRCT20211015052775N1.